2003
DOI: 10.1001/jama.290.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Health-Related Quality of Life Among Adult Latino Primary Care Patients Living in the United States With Previous Exposure to Political Violence

Abstract: OLITICAL VIOLENCE IS INCREASingly recognized as a threat to public health and includes many types of violence such as war, torture, forced disappearances, and extrajudicial killings. 1-3 Much research on the long-term health consequences of political violence has focused on torture and not on the wider problem of political violence experienced by immigrants and refugees. 4,5-8 This is especially pertinent to immigrants from Mexico, Central America, and South America, who experienced war-related violence and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 39 publications
11
135
1
11
Order By: Relevance
“…In a predominantly female clinical sample surveyed between 2001 and 2002, Eisenman reported a high percentage of participants from Mexico, El Salvador, Guatamala, and other groups who experienced political violence (54%), including 8% who reported torture. 54 Higher levels of psychological distress were reported in that sample, and statistically significant increases were found among those reporting political violence (36% versus 20% for depression, 18% versus 8% for posttraumatic stress symptoms). 54 The response of Latinas to recent and remote exposures in our cohort were more similar to results found by Aisenberg who assessed community violence in an urban US neighborhood.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a predominantly female clinical sample surveyed between 2001 and 2002, Eisenman reported a high percentage of participants from Mexico, El Salvador, Guatamala, and other groups who experienced political violence (54%), including 8% who reported torture. 54 Higher levels of psychological distress were reported in that sample, and statistically significant increases were found among those reporting political violence (36% versus 20% for depression, 18% versus 8% for posttraumatic stress symptoms). 54 The response of Latinas to recent and remote exposures in our cohort were more similar to results found by Aisenberg who assessed community violence in an urban US neighborhood.…”
Section: Discussionmentioning
confidence: 67%
“…54 Higher levels of psychological distress were reported in that sample, and statistically significant increases were found among those reporting political violence (36% versus 20% for depression, 18% versus 8% for posttraumatic stress symptoms). 54 The response of Latinas to recent and remote exposures in our cohort were more similar to results found by Aisenberg who assessed community violence in an urban US neighborhood. As reported by Aisenberg, we found no statistically significant associations between witnessing neighborhood violence and the experience of depression among Latinas.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the majority of people expressed optimism and self-efficacy regarding their ability to function in a terrorist attack. Similarly, a study of Latino primary care patients in the United States revealed that of those who had experienced political violence in their homeland, 18% met the criteria for PTSD (Eisenman, Gelberg, Liu, & Shapiro, 2003). The lifetime prevalence of PTSD in the general population of the United States is reported to be 5% for men and 10% for women (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995).…”
Section: Manual Of Mental Disorders (Dsm) (Americanmentioning
confidence: 99%
“…However, our current knowledge base is limited. Prior research suggests that only a very small proportion of individuals who have been exposed to political violence report this to their health care providers (Carey et al, 2003;Eisenman et al, 2003).…”
Section: Racial and Political Violence And Mental Healthmentioning
confidence: 99%